Efficiency of Public Goods Provision in Space - Travis Warziniack (University of Heidelberg, Department of Economics, 2009)
This article incorporates a political decision process into an urban land use model to predict the likely location of a public good. It fills an important gap in the literature by modeling the endogenous location of open space. The article compares open space decisions made under a majority-rules voting scheme with welfare-improving criterion and finds households tied to a location in space compete against each other for public goods located nearer them. Significant differences emerge between the two decision criteria, indicating that requiring referenda for open space decisions is likely to lead to inefficient outcomes. Specifically, many open space votes are likely to fail that would lead to welfare improvements, and any open space decisions that do pass will require amenities larger than needed to achieve the social optimum. The more dispersed and large the population, the larger is the gap between the socially efficient level and the level needed for a public referendum to pass.
Keywords: D23; L29; M10; 330; organizational slack; antecedents; dispositional requirements; resources; Öffentliche Güter; Regionalökonomik; Landnutzung; Referendum; Abstimmungsregel; Theorie